2017
DOI: 10.1080/00325481.2017.1315290
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bromocriptine-QR therapy on glycemic control in subjects with type 2 diabetes mellitus whose dysglycemia is inadequately controlled on insulin

Abstract: Objective: The concurrent use of an insulin sensitizer in type 2 diabetes mellitus (T2DM) patients with inadequate glycemic control on basal-bolus insulin may help improve glycemic control while limiting further insulin requirement. Bromocriptine-QR (B-QR), a quick release, sympatholytic, dopamine D2 receptor agonist therapy for T2DM, is a postprandial insulin sensitizer. This study evaluated the effect of B-QR on dysglycemia in T2DM subjects with suboptimal glycemic control on basal-bolus insulin plus metform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
1
21
1
Order By: Relevance
“…It is not clear if L-DOPA treatments to the eye would require such large dosing. Finally, bromocriptine treatment in Type II diabetes has already been shown to improve glucose control (Chamarthi and Cincotta, 2017), increase fat loss (Meier et al, 1992), and prevent progression of kidney disease (Mejia Rodriguez et al, 2013), suggested that systemic disease might benefit with dopamine agonist treatment, in addition to potential retinal benefits.…”
Section: Dopamine Based Therapiesmentioning
confidence: 99%
“…It is not clear if L-DOPA treatments to the eye would require such large dosing. Finally, bromocriptine treatment in Type II diabetes has already been shown to improve glucose control (Chamarthi and Cincotta, 2017), increase fat loss (Meier et al, 1992), and prevent progression of kidney disease (Mejia Rodriguez et al, 2013), suggested that systemic disease might benefit with dopamine agonist treatment, in addition to potential retinal benefits.…”
Section: Dopamine Based Therapiesmentioning
confidence: 99%
“…A relationship between T2DM and L-dopa therapy [71, 73] and dopaminergic agonists, especially bromocriptine [74, 76, 77, 8083], has been detected. In trials with rodents, L-dopa therapy caused a decrease in insulin secretion in glucose tolerance tests due to the dopamine increase in pancreatic cells [173].…”
Section: Discussionmentioning
confidence: 99%
“…An additional two records were identified by searching the reference lists of included trials and reviews. As illustrated in the PRISMA flow diagram (Appendix S1), 28 17 publications [10][11][12][29][30][31][32][33][34][35][36][37][38][39][40][41][42] reporting the effect of bromocriptine or cabergoline on T2D in nine trials 11,12,[29][30][31]33,37,38,41 were identified. A total of 3456 participants were randomized and 3433 were included in the final analyses.…”
Section: Bibliographical Search and Trial Characteristicsmentioning
confidence: 99%